Los estilos de liderazgo y el resultado de estudiantes de maestrías en la Universidad Nacional Mayor de San Marcos - Cuba Rosales, Luis Alexis Fernando (2025)
The purpose of this paper is to analyze the relationship between leadership styles and academic performance of working students at the Universidad Nacional Mayor de San Marcos, as well as to explore possible differences according to the work sector to which they belong. For this purpose, the concepts of transformational, transactional and laissez-faire leadership proposed by different authors were used. Data collection was carried out using the well-known Multifactor Leadership Questionnaire (MLQ-5X) developed by Bruce Avolio and Bernard Bass, applied in digital format. This study is descriptive-correlational in nature, with a non-experimental, cross-sectional design. The sample included graduate students working in both the public and private sectors. Spearman's Rho and Student's T tests were used for statistical analysis. The results show that transformational leadership has a significant impact on academic performance compared to the other styles analyzed. Also, differences in leadership practices between the two sectors were identified. Finally, recommendations are proposed to improve the application of leadership and further future research.